2013
DOI: 10.1186/1750-1164-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the SPY intraoperative perfusion assessment system to reduce ischemic complications in immediate postmastectomy breast reconstruction

Abstract: BackgroundThe quality and viability of mastectomy flaps remain a central challenge in reconstructive surgery, particularly for immediate breast reconstruction. Insufficient perfusion in tissue flaps is a leading cause of early complications following reconstructive procedures, and clinical judgment alone is not completely reliable for the assessment of flap viability. Accurate and reliable intraoperative methods for assessment of tissue perfusion are needed to help surgeons identify tissue at risk for ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 61 publications
3
69
0
Order By: Relevance
“…1). After detailed examination of 30 full‐text articles, 18 studies7 19, 20 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, including 2077 patients, were included in this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). After detailed examination of 30 full‐text articles, 18 studies7 19, 20 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, including 2077 patients, were included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…One was to compare rates of mastectomy necrosis and other complications, such as reoperation rates, and clinical outcomes between the techniques used ( Table 1). Seven case series7 28, 29, 30, 31, 32 34 and one cohort study33 used this approach. The alternative approach in seven prospective cohort studies19 20, 35, 36, 37, 38, 39 was to evaluate flap perfusion using the intraoperative modalities and to record the predicted areas of necrosis using photographic documentation or video recording.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…56,86,98,99 Both SPY ® and SPY Elite ® generate quantitative perfusion values based on fluorescence intensity detected in the tissue. [99][100][101] This system has been investigated for multiple intraoperative uses during breast reconstruction, including perfusion assessment of mastectomy skin flaps, Open Access Surgery 2014:7 submit your manuscript | www.dovepress.com Dovepress Dovepress 6 Ferzoco pedicle flaps, and free-tissue transfers, 56,98,99,[101][102][103] and in head and neck 104 and abdominal wall reconstruction surgeries. 100 The clinical utility of the SPY ® system in breast surgery has been described by Newman and Samson, 102 who reported that perfusion problems identified with SPY ® in four of eight patients undergoing free-flap breast reconstruction led to interventions that prevented flap necrosis in three patients.…”
Section: Spy ® /Spy Elite ®mentioning
confidence: 99%
“…If the implant is accepted easily and without tension, a temporary suture is placed, and vascular skin flap perfusion is assessed with intravenous injection of indocyanine green fluorescence angiography using the SPY Elite protocol (Novadaq Technologies, Inc, Mississauga, ON), as previously reported by several authors. [27][28][29][30] If vascular perfusion is deemed adequate using accepted criteria, 28,29 the lateral pectoralis major muscle is reflected and a subpectoral cautery dissection performed with the inferior and inferomedial attachments of the pectoralis major (PM) to the ribs and sternum is released. It is critical to elevate the PM sufficiently in a cephalad direction to allow for adequate mobilization and proper redraping and insetting of the pectoralis/ADM composite with undue tension once constructed.…”
Section: Surgical Techniquementioning
confidence: 99%